Anthropomorphic Representation and the Relics - Račiūnaitė, Tojana (Problemos, 2020)
The concepts of representation and perception, which are specially employed and contextualised in this article, were introduced for cultural reflection by Arūnas Sverdiolas. Pamėklė is a Lithuanian equivalent of “simulacrum,” which can be associated with images that are distinguished by a doll effect and provoke spectator-participant reaction and involvement, and can therefore be associated with reckoned instruments of experience. Another strategy for representing a person encompasses the phenomenon of relics, the fragmentary remains of the body. The article shows how these kinds of anthropomorphic representations of the body can be detected individually and how they can co-exist in a hybrid structure. The example of such a structure we can find in the exposition of relics from the body of St Boniface in the church in Valkininkai.